60.6k views
2 votes
-2(4r - 6) Mathhhhhhhhh pls

User PRGSTony
by
4.5k points

2 Answers

4 votes

Answer: -8r + 12

============================================

Step-by-step explanation:

The outer term -2 is multiplied by each term inside

  • -2 times 4r = -8r
  • -2 times -6 = 12

Then those results are added to get -8r + 12 as our final answer. We cannot combine these terms because they are not like terms.

I used the distribution property, also known as the distributive property.

That says a*(b-c) = a*b - a*c

In this case, a = -2, b = 4r, and c = 6.

User Rondo
by
4.8k points
3 votes

Answer: -8r+12

Step-by-step explanation:

User Brian Jew
by
4.4k points